Penerapan Asas Keterbukaan Pada Pemerintah Desa Dasan Tapen Kecamatan Gerung Kabupaten Lombok Barat - Dita Misriani; R. Rispawati; Bagdawansyah Alqadri; Y. Yuliatin (Public Inspiration : Jurnal Administrasi Publik, 2023)
This study aims to describe the role of the village government in applying the principle of openness to village government, the factors that influence the implementation of the principle of openness, and the village government's efforts to apply the principle of openness and transparency in Dasan Tapen Village, Gerung District, West Lombok Regency. A qualitative approach with a descriptive type is applied in this study. Therefore, the subjects in this study were the village head, the secretary of the village finance division and 2 informants from religious and community leaders. The collected data was analyzed through data reduction, data presentation, and drawing conclusions. The analyzed data was tested again through source and time triangulation. The results of this study indicate that the village government's strategy in implementing the principle of openness in the village government of Dasan Tapen village, Gerung district, West Lombok regency included the information preparation, information processing and village apparatus services. Factors that influenced the application of the principle of openness to village government include internal factors such as facilities and human resources. While the external factors consist of cooperation, community ideas or ideas, and the leadership of the village head. The implementation of the principle of openness in the village government is by implementing Law Number 6 of 2014 concerning villages.